Analysis of Factors Influencing the Implementation of K3 on Employees at the Oksibil Community Health Center - Manurung, Andika Ferdinan; Yusuf, Yusuf; Muhammad Rifai (Jurnal Kesehatan dan Kedokteran, 2026)
Clinical laboratory services are crucial for public health, requiring adequate facilities, modern technology, and well-trained personnel to meet safety standards. In line with the Indonesian Minister of Health Regulation No. 66 of 2016, Occupational Safety and Health (OSH) systems are essential to safeguard hospital staff, patients, visitors, and the environment by preventing accidents and illnesses. Objective: This study aims to investigate the relationship between Occupational Safety and Health Management components (K3 Promotion, Training, Supervision, Investigation, Reporting) and workplace accidents in the laboratory at Dr. Wahidin Sudirohusodo General Hospital, Makassar. Methodology: A descriptive analytical approach with a cross-sectional design was used, involving 110 laboratory staff selected through total sampling. Data were collected using structured questionnaires and analyzed with the Chi-Square statistical test. Findings: A significant relationship was found between Training and workplace accidents (ρ = 0.041), while K3 Promotion (ρ = 0.141), Supervision (ρ = 0.153), Investigation (ρ = 0.575), and Reporting (ρ = 0.078) did not show significant associations. Implications: This study emphasizes the need to re-socialize OSH practices to all hospital staff, highlighting that work accidents should include all incidents, not just needle-stick injuries, and must be reported for preventive measures. Originality: This research offers new insights into the importance of training in improving OSH outcomes in hospital laboratories, providing valuable guidance for optimizing OSH management in healthcare settings.